Arctic (palaeo) river discharge and environmental change: evidence from the Holocene Kara Sea sedimentary record. - Stein, Ruediger; Dittmers, Klaus Hauke; Fahl, Kirsten; Kraus, Matthias; Matthiessen, Jens; Niessen, Frank; Pirrung, Michael; Polyakova, Ye I; Schoster, Frank; Steinke, Tatjana; Fütterer, Dieter K (PANGAEA, 2004)
In this paper, we summarize data on terrigenous sediment supply in the Kara Sea and its accumulation and spatial and temporal variability during Holocene times. Sedimentological, organic-geochemical, and micropaleontological proxies determined in surface sediments allow to characterize the modern (riverine) terrigenous sediment input. AMS-14C dated sediment cores from the Ob and Yenisei estuaries and the adjacent inner Kara Sea were investigated to determine the terrigenous sediment fluxes and their relationship to paleoenvironmental changes. The variability of sediment fluxes during Holocene times is related to the post-glacial sea-level rise and changes in river discharge and coastal erosion input. Whereas during the late/middle Holocene most of the terrigenous sediments were deposited in the estuaries and the areas directly off the estuaries, huge amounts of sediments accumulated on the Kara Sea shelf farther north during the early Holocene before about 9 cal kyr BP. The maximum accumulation at that time is related to the lowered sea level, increased coastal erosion, and increased river discharge. Based on sediment thickness charts, echograph profiles and sediment core data, we estimate an average Holocene (0–11 cal kyr BP) annual accumulation of 194,106 t/yr of total sediment for the whole Kara Sea. Based on late Holocene (modern) sediment accumulation in the estuaries, probably 12,106 t/yr of riverine suspended matter (i.e. about 30% of the input) may escape the marginal filter on a geological time scale and is transported onto the open Kara Sea shelf. The high-resolution magnetic susceptibility record of a Yenisei core suggests a short-term variability in Siberian climate and river discharge on a frequency of 300–700 yr. This variability may reflect natural cyclic climate variations to be seen in context with the interannual and interdecadal environmental changes recorded in the High Northern Latitudes over the last decades, such as the NAO/AO pattern. A major decrease in MS values starting near 2.5 cal kyr BP, being more pronounced during the last about 2 cal kyr BP, correlates with a cooling trend over Greenland as indicated in the GISP-2 Ice Core, extended sea-ice cover in the North Atlantic, and advances of glaciers in western Norway. Our still preliminary interpretation of the MS variability has to be proven by further MS records from additional cores as well as other high-resolution multi-proxy Arctic climate records.
Distribution of grain size and clay minerals in surface sediments of the Kara Sea (Fig 4, 5)
Keywords: Akademik Boris Petrov; BP00; BP00-02/02; BP00-05/04; BP00-07/08; BP00-08/03; BP00-09/03; BP00-13/03; BP00-14/02; BP00-15/03; BP00-16/03; BP00-17/02; BP00-22/03; BP00-26/03; BP00-28/01; BP00-29/02; BP00-30/01; BP00-31/01; BP00-35/03; BP00-36/08; BP00-38/01; BP01; BP01-28/05; BP01-29/01; BP01-30/05; BP01-33/01; BP01-34/05; BP01-36/01; BP01-41/05; BP01-47/02; BP01-48/05; BP01-51/04; BP01-57/01; BP01-60/01; BP01-61b/05; BP01-63/01; BP01-64/04; BP01-66/04; BP01-68/04; BP01-70/05; BP01-72a/02; BP01-73/04; BP01-76/01; BP99; BP99-05/01; BP99-24/06; BP99-25/06; BP99-28/05; BP99-29/05; BP99-30/06; BP99-31/06; BP99-32/06; BP99-38/05; BP99-39/05; Chlorite; DEPTH, sediment/rock; GC; Giant box corer; GKG; Grain size, sieving; Grain size, sieving/settling tube; Gravity corer; Illite; Kaolinite; Kara Sea; MUC; MultiCorer; OKEAN; Okean Grab; Quaternary Environment of the Eurasian North; QUEEN; Sand; Siberian River Run-Off; Silt; SIRRO; Size fraction < 0.002 mm, > 9 phi, clay; Smectite; X-ray diffraction TEXTUR, clay fraction